Knowledge Level of Improved Buffalo Husbandry Practices in Peri-urban areas of Surat city of Gujarat (Indian Journal of Animal Production and Management, 2024)
A field survey was conducted in the Peri-urban areas of Surat city of Gujarat to assess the knowledge  level of randomly selected 50 buffalo farm owners about improved buffalo husbandry practices. The  analysis of data collected by personal interview method revealed that majority of buffalo owners had  medium knowledge level on different aspects of improved buffalo husbandry practices viz. 76% for  feeding, 56% for breeding, 72% for general management and 50% for health care. The overall  knowledge levels of the respondents in improved buffalo husbandry practices fall under low, medium  and high categories are 16%, 68% and 16%, respectively. The knowledge index of different aspect  of improved buffalo husbandry practices of feeding, breeding, general management and health care  were 42.50, 67.575, 45.50 and 54.25%, respectively and overall knowledge index of improved buffalo  husbandry practices was 52.50 % in the study area.
Keywords: Buffalo; husbandry; knowledge; peri-urban areas